ESTABLISHMENT AND DEVELOPMENT OF SCIENTIFIC SCHOOL OF RAS ACADEMICIAN E.A. LUZHNIKOV - M. S. Khubutiya; Y. S. Goldfarb; S. A. Kabanova; P. M. Bogopolsky; M. M. Potskhveriya (Неотложная медицинская помощь, 2017)
The scientific school of the academician of the Russian Academy of Science E.A. Luzhnikov is the largest and most authoritative school in clinical toxicology in Russia, uniting about 150 scientists whose research continues and develops ideas, views and methodological approaches suggested by the teacher. Scientific achievements of E.A. Luzhnikov school have a high degree of relevance and novelty. Some studies of the school are of a fundamental nature. The feature of the scientific school of E.A. Luzhnikov is its great scientific and organizational activity, such as establishment and development of toxicological services in the country, which significantly improved the results of treatment for acute poisonings in Russia.